PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPS DI SDN PANGILEN 3 SAMPANG - Abdussalam; Muhammad Jefri Efendi; Ihwan Firmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social studies are important for forming students' social understanding and critical skills and increasing student achievement with the implementation of PJBL. The study aims to determine the success and influence of the PJBL model on social studies learning outcomes and to evaluate the achievement of student learning outcomes at SDN Pangilen 3 Sampang. Quantitative experimental research uses a one group pretest-posttest design. Data were analyzed by tests and observations, using normality, homogeneity, and t-test tests to significantly measure the effectiveness of PJBL. The results of the study showed: The implementation of PJBL as a whole was in the sufficient category and needed improvement in reflection and collaboration. Of the 16 fourth grade students, 43.75% achieved KKM 70 in the pre-test with an average of 69.25. After learning a certain model, 93.75% achieved KKM, the average increased to 72.38, and the scores were more even, indicating an increase in mastery of social studies material. The normality and homogeneity tests of the data were met. The p value of 0.017 indicated by the partial test explains that there is a significant difference so that this explains that PjBL affects students' social studies learning achievement. Conclusion: The implementation of PJBL is quite effective with increasing mastery of social studies material, but reflection and collaboration need to be improved.